Pemberdayaan Masyarakat melalui Edukasi GEMA CERMAT: Penggunaan Antibiotik Menggunakan Media Booklet dengan Metode CBIA (Cara Belajar Insan Aktif) - Musdalipah Musdalipah; Nur Saadah Daud; Eny Nurhikma; Karmilah Karmilah; Nirwati Rusli; Reymon Reymon; Selfyana Austin Tee; Muhammad Azdar Setiawan; Yulianti Fauziah; Rifcha Selviana Puput; Muh. Ilyas Yusuf; Nurhikma Nurhikma (Universitas Lancang Kuning, 2022)
The high use of inappropriate antibiotics in the community is due to a lack of knowledge about antibiotics, thereby increasing the problem of antibiotic resistance. These problems can be overcome through community empowerment with Gema Cermat education through booklet media using the CBIA method. The Smart Society Using Drugs (Gema Cermat) is one of the educational efforts to increase public awareness, concern and understanding about how to use drugs properly and correctly. The purpose of the activity is to increase knowledge about the use of antibiotics using booklet media in the Punggolaka village, Puuwatu district, Kendari City. The method of activity is through Gema Cermat education with the CBIA method, pre and posttest questionnaires, booklets, pocket books, and power point presented by the pharmacist. The results show that an increase in knowledge in the good category of 100%. This is shown in the knowledge of the community at the pretest of 10.25% and increased by 100% after the posttest. Based on the results of the activity, it was concluded that Gema Cermat activities could increase public knowledge